Evaluating Atmospheric Pressure Plasma Treatments for Suppression of White Bread’s Mold Growth (ELEKTRIKA- Journal of Electrical Engineering, 2025)
Food wastage accounts for up to 44% of global waste, posing a serious economic and environmental concern. A major contribution to this issue is microbial contamination, which leads to food spoiled and poses health risks to humans. White bread, a dietary staple consumed worldwide, is particularly vulnerable to microbial contamination – despite an estimated global production of 100 million tons annually, hundreds of tons are discarded daily due to microbial spoilage, particularly mold. Thus, to address this issue, the use of atmospheric pressure plasma (AAP) as a non-thermal food preservation technology is explored in the present study. Two types of plasma generators: dielectric barrier discharge (DBD) and atmospheric pressure plasma jet (APPJ) were used to treat white bread samples. The progression of mold growth on the samples was observed for seven days after treatment durations ranging from 60 to 120 seconds. On day seven, the percentages of mold growth were 51.23% and 21.39% for samples A1 and A2, respectively, while untreated samples exhibited 68.88% mold growth. Meanwhile, sample D1, which was treated with DBD plasma, demonstrated remarkable resistance, with only 1.70% mold growth progression.  The optimal treatment parameters identified were 13.6 kV for 120 seconds for DBD and 16.1 kV for 120 seconds for APPJ. Under these optimal discharge conditions, both plasma generators significantly suppressed the progression of mold growth progression, with DBD treatment showing superior performance. The findings demonstrate the potential of plasma-based treatments to effectively extend the shelf life of white bread and reduce food wastage.
Keywords: Food treatment; white bread; mold decontamination; atmospheric pressure plasma jet; dielectric barrier discharge